High Blood Pressure in Adolescents of Curitiba: Prevalence and Associated Factors - Bozza,Rodrigo (2016)
Abstract Background: Arterial hypertension is a major public health problem and has increased considerably in young individuals in past years. Thus, identifying factors associated with this condition is important to guide intervention strategies in this population. Objective: To determine high blood pressure prevalence and its associated factors in adolescents. Methods: A random sample of 1,242 students enrolled in public schools of the city of Curitiba (PR) was selected. Self-administered questionnaires provided family history of hypertension, daily energy expenditure, smoking habit, daily fat intake, and socioeconomic status. Waist circumference was measured following standardized procedures, and blood pressure was measured with appropriate cuffs in 2 consecutive days to confirm high blood pressure. Relative frequency and confidence interval (95%CI) indicated high blood pressure prevalence. Bivariate and multivariate analyses assessed the association of risk factors with high blood pressure. Results: The high blood pressure prevalence was 18.2% (95%CI 15.2-21.6). Individuals whose both parents had hypertension [odds ratio (OR), 2.22; 95%CI 1.28-3.85] and those with high waist circumference (OR, 2.1; 95%CI 1.34-3.28) had higher chances to develop high blood pressure. Conclusion: Positive family history of hypertension and high waist circumference were associated with high blood pressure in adolescents. These factors are important to guide future interventions in this population.